DIFFERENTIATION OF NULLITY AND INVALIDITY OF ADMINISTRATIVE ACTS: COMPARATIVE LEGAL ANALYSIS AND DIRECTIONS IMPROVEMENT OF LEGISLATION - Нормухамедова Сурайёхон Бобир қизи (Modern American Journals, 2026)
Legal acts of management are one of the fundamental stages in the implementation of management functions to solve existing problems and achieve goals. Legal acts, in general, contribute to the implementation of activities in various sectors - economic, customs, cultural, social, etc.